Pengaruh Bimbingan Belajar Oleh Orang Tua Dan Motivasi Belajar Bagi Siswa Terhadap Tanggung Jawab Belajar Siswa Kelas V SD Negeri Tegalglagah 04 Bulakamba Brebes - Langgeng Windystia Restu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Responsibility in the learning process is very important to be carried out. Students are still low on schoolwork. The purpose of this study is to analyze the influence of tutoring by parents and learning motivation for students both partially and simultaneously on the learning responsibilities of elementary school students. This research uses quantitative approach using explanatory research through associative research. The research data used is subject data in the form of opinions, attitudes, experiences or characteristics using questionnaires. Known coefficient of correlation R of 0.623, which states the amount of contribution of independent variables of tutoring by parents (X1) and motivation of learning for students (x2) of 62.30% in explaining the variability of dependent variables of student learning responsibility (Y) at SD Negeri Tegalglagah 04 Bulakamba Brebes. Based on the regression equation 25.688 + 0.166 X1 + 0.107 X2. It can be concluded that the tutoring (X1) and learning motivation (X2) have a positive and significant influence partially and simultaneously on the responsibility of learning for students (Y) grade V at Tegalglagah State Elementary School 04, Bulakamba, Brebes.